Financial contribution and ecclesiastical sustainability: The program of Christian Stewardship in IECLB - Afonso Butzke, Paulo (Vox Scripturae - Revista Teológica Internacional, 2014)
Financial sustainability worries the church since its beginnings. Thus, throughout history, various models emerged fomenting the financial contribution of members as responses of faith and gratitude for the blessings received. One of these models is of stewardship, whose implantation in the Brazilian Church of Lutheran Confession (IECLB), commencing at the 70’s of the XXth century, is presented in this work. Firstly, it is described the appearance of the concept of stewardship in the bosom of the XIXth century North-American Protestantism and its reception by the Latin-American Lutheranism, especially the Brazilian. After the assimilation of the stewardship theology, the IECLB sought means to implant the model through the installation of a Stewardship Secretary in 1963, in charge of disclosing it to the communities, of training the necessary leaderships and of follow the accomplishment of the so called “stewardship action”, intensive program of 3 to 4 years of integral evangelization that culminates in the annual commitment of the members in engaging in diverse communitarian and missionary works and in the financial commitment. In many communities and parishes of IECLB, the stewardship program brought great impulses for the communitarian life and its mission, exemplified in this work through the cases of the parishes of Novo Hamburgo/RS and Joinville/SC. Despite the great spiritual development provided, the stewardship program suffered critiques and ended up disappearing in the following years. It remains alive, however, in the historic memory of IECLB as a blessed experience in the search for ecclesiastic sustainability that still has much to teach.